Key Topics in Public Water Utility Reform - Ginneken, Meike van (World Bank, Washington, DC, 2012)
Urban water supply services have traditionally been provided by state-owned, water utilities. In the past decades, many governments have tried to turn state-owned water utilities into effective and viable organizations with mixed success. Why have some public utilities become more efficient service providers, while others have not been able to break the vicious cycle of low performance and low cost recovery? The World Bank report "key topics in public water utility reform" presents a framework of attributes of well functioning utilities and how they have introduced key institutional measures. It thus aims to help water and sanitation sector practitioners to choose and apply public utility reform approaches.